Subic Bay Living Lab for building research - Feliciano, Renzo C.; Ramos, Grace C. (Quezon City College of Architecture, University of the Philippines Diliman, 2017)
The Subic Bay Living Lab is a proposed institutional project in the Subic bay CBD. Based on the issues and potentials of the Subic Bay area, a set of agenda was created and from it a functional response in the form of a space program. A specific site was then chosen based on the facility's immediate needs. An awareness of the area's developmental vision presents the premise of future expansion for both the CBD and the facility itself, providing the direction for the approach to the facility's design. The facility has four main components : the Information Center, the Training Center, the Residences, and the Research Laboratory which focuses on research and development of innovative building systems, construction processes, and moern technologies. Intended for interested locals, the residences aim to provide the research lab information on how the technologies in develops can affect how its residents live : in real-life, real-time contexts; in turn, these technologies, through monitoring and feedback, can be improved if needed. In addition to incorporating sustainable building systems and technologies to its design, the facility explores the concept of adaptability in both use and capacity through modularity. Finally, presented as the primary design problem, it studies different design strategies in integrating different uses in one facility, most notably the residences and the laboratory as a response to the key issue of ethics.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman